"The Only True People" : Linking Maya Identities Past and Present - LeCount, Lisa J. (Lisa Jeanne), 1955-; Beyyette, Bethany J. (Book collections on Project MUSE., 2017)
"A timely and rigorous examination of ethnicity among the ancient Maya, focusing on ethnogenesis and exploring the complexities of Maya identity--how it developed, how it emerged and how it continues to change. Challenges the notion of ethnically homogenous "Maya peoples" for their region and chronology"--Provided by publisher.